The Doha Round: Virtuous circle or infinite loop? - Laborde Debucquet, David (International Food Policy Research Institute, 2017)
This chapter aims to provide a narrative of the 15 years of the Doha Round negotiations and to quantitatively illustrate how these negotiations have tried to reach a compromise regarding the market access pillar of the agricultural talks.